Implementation of Irrigation Management Policy in West Java Province - Restuardy Daud; Hadi Prabowo; Dahyar Daraba; Mansyur Achmad; Mendra Wijaya (International Journal of Economics Development Research (IJEDR), 2024)
The phenomenon of government management within the framework of decentralization politics in Indonesia is the basis for this study to reveal how the implementation of government affairs policies is carried out in irrigation management which is the authority of the regional government with various actors involved in it, both from the government itself, private institutions (private sector), and civil society. This study aims to analyze, compile a synthesis, and explain qualitatively the implementation of irrigation management policies in West Java province. This study uses a qualitative research method with a descriptive approach. The results of the study indicate that the implementation of public policy is essentially an activity to distribute policy outputs (to deliver policy output) carried out by implementors to target groups (target groups) as an effort to realize policy objectives. Policy objectives are expected to emerge when policy output can be accepted and utilized properly by target groups so that in the long term the results of the policy can be realized. Then the conclusion of this study is the conclusion compiled based on the results of the research and discussion of the implementation of irrigation management policies in West Java province is as follows: The irrigation management policy in West Java province is stipulated through West Java Provincial Regulation Number 4 of 2008 concerning Irrigation which regulates the development and management activities of the provincial authority irrigation system and can be used as a guideline for the preparation of district/city regional regulations concerning irrigation.